An Analysis of Consumer Purchase Decisions Influenced by Product Quality, Live Shopping, and Product Information - Azhari, Azlan; Ridha, Achmad; Hasnidar, Hasnidar (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study investigates the impact of product quality, live shopping, and product information on consumer purchasing decisions, with a specific focus on Nanotech Protection automotive care products sold through TikTok Shop. The research investigates whether each factor, individually and collectively, significantly influences the shaping of consumer behavior in a digital commerce setting. Research Method: This study adopted a quantitative research approach, the study collected data from 85 consumers in Makassar City who had previously purchased Nanotech Protection products via TikTok Shop. This analysis was supported by validity and reliability testing, as well as t-tests, F-tests, and R-square analysis, all processed using SPSS version 27 to ensure statistical accuracy and robustness. Results and Discussion: The results show that product quality, live shopping, and product information have a statistically significant and positive effect on consumer purchase decisions, with product quality being the most influential factor. Implications: The study offers valuable insights for marketers, particularly in digital commerce, on how to strategically integrate high product standards with engaging live content and accurate product information. Future research is suggested to expand the geographical scope and adopt longitudinal approaches.